PENTAKOSTA MENURUT INJIL YOHANES: STUDI EKSEGETIS YOH. 20:22-23 - Eklepinus Jefry Sopacuaperu (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2020)
This article aims to elaborate the account of the disciples’ experience of pentacost according to the gospel of John. On one hand, the study purpose to introduce the readers with the occurance of pentacost that took place during Jesus appearance to the disciples as narrated in gospel of John. On the other hand, the study intends to waked readers awareness to explore the contrasts and delve the uniqueness between the narratives of pentacost as accounted in Acts 2:1-13 and John 20:22-23. Therefore, this article is an exegetical study that focuses on the study of the text and its intercorrelation to the context of the text. Furthermore, it is a great hope that this writing will open a space for theological discourse.